PASSIONATE DOMINANT OF THE STYLE OF ULAS SAMCHUK’S SHORT PROSE - Maftyn, Nataliia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2025)
The proposed article is devoted to the analysis of the ideological and artistic features of Ulas Samchuk’s short prose from the collection “Paradise Found”. The aim is to reveal the interaction of the ideological and rhetorical code of the works of the collection with the author’s worldview dominant as well as its determination of the imagery of the short stories. The research methodology involves inductive-empirical, objective-analytical and ethno-psychological studies as well as postcolonial studies. Thus, it was found that the ideological and rhetorical code of Ulas Samchuk’s collection “Paradise Found” is motivated by a sense of patriotism, love and longing for Ukraine, anxiety for its fate. Therefore, the basis of the author's short story thinking is an ethno-psychological paradigm that determines both genre-compositional and stylistic features. It is the ethno-psychological factors (the desire to live inherent in the character of a Ukrainian, professing the ideal of the rank – “Vita maхima et heroika” (O. Kulchytskyi), “intimate connection with the earth” (V. Yaniv), individualism and the acute need for freedom) become the basis of the artistic conflict of individual short stories in the collection; they are realized through the antithesis of the main features of the Ukrainian and Moscow mentality (short stories “Sylvester”, “For Real”). The “organic connection with the historical fate of the people”, the desire to “include” the chronotope of the homeland in emigration everyday life, filling them with meaning in this way, is caused, in our opinion, by such a compositional feature of Samchuk’s short stories as “two-dimensionality”: the presence of an “eventual”, plot part, which deals with emigrant life, and a “visionary”, which constitutes memories of Ukraine and carries the main ideological load.